Cadmium affects the regeneration of the leafy vegetable Talinum portulacifolium stem cuttings in nutrient solution - Thangavelu; Selvam (Anales de Biología, 2020)
We investigated the effect of various concentrations (0.0-5.0 ppm) of cadmium (Cd) on the regeneration ability; morphological characteristics and Cd accumulation in the leafy vegetable Talinum portulacifolium stem cuttings grown in hydroponic culture. Cd delayed sprouting of stem cuttings by 7%, callusing by 8% and rooting by 38%. Different Cd concentrations significantly affected fresh and dry weight of plant parts except roots. Accumulation of Cd was more in the stems than in leaves (2.22 vs 0.57 ppm). The calculated tolerance index ranged from 59% to 88%. Based on the observations it was concluded that Cd interferes with the regeneration of T. portulacifolium stem cuttings and imply concerns on the consumption and therapeutic use of this leafy vegetable growing on polluted soils.